A molecule away from madness : tales of the hijacked brain - Peskin, Sara Manning (W.W. Norton & Company, Inc., 2022)
"A neurologist regales readers with extraordinary stories of the brain under siege. Our brains are the most complex machines known to humankind, but they have an Achilles heel: The very molecules that allow us to exist can also sabotage our minds. Here are true accounts of unruly molecules and the diseases that form in their wake, from total loss of inhibitions to florid psychosis to compulsive lying. Cognitive neurologist Sara Manning Peskin demystifies the most curious neurological phenomena through the perspective of patients, researchers, and science. She introduces us to a woman stuck in The Walking Dead, a family wracked with Alzheimer's disease, and an entire region gripped by a baffling epidemic. By tracing the molecular causes for neurologic diseases, Peskin highlights cutting-edge developments in cognitive research, making the case that these are the stories that will one day teach us how to cure dementia and other diseases of the brain. A Molecule Away from Madness offers a captivating, singular view of the human brain"--